1986
DOI: 10.3171/jns.1986.65.2.0203
|View full text |Cite
|
Sign up to set email alerts
|

Neurosurgical complications after apparently minor head injury

Abstract: A small number of patients with an apparently minor head injury will develop a life-threatening intracranial hematoma that must be rapidly detected and removed. To assess the risk of a significant intracranial neurosurgical complication after apparently minor head injury, the authors collected data prospectively on 610 patients who had sustained a transient posttraumatic loss of consciousness or other neurological function and who had a Glasgow Coma Scale (GCS) score of 13, 14, or 15 in the emergency room. Sku… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
91
1
7

Year Published

1992
1992
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 255 publications
(104 citation statements)
references
References 24 publications
5
91
1
7
Order By: Relevance
“…Because of the relationship between these two variables, prolonged loss of consciousness was not identified as an independent predictor in the multivariate analysis. Because prior studies 15,29,30 have suggested that loss of consciousness may be associated with intracranial injury, we think that the history of loss of consciousness should still be considered in the evaluation of intracranial injury in children. Although we achieved telephone follow-up of 95% of the patients discharged home from the emergency department, the collected information reflects the general well-being of the child in the week after the injury.…”
Section: Discussionmentioning
confidence: 99%
“…Because of the relationship between these two variables, prolonged loss of consciousness was not identified as an independent predictor in the multivariate analysis. Because prior studies 15,29,30 have suggested that loss of consciousness may be associated with intracranial injury, we think that the history of loss of consciousness should still be considered in the evaluation of intracranial injury in children. Although we achieved telephone follow-up of 95% of the patients discharged home from the emergency department, the collected information reflects the general well-being of the child in the week after the injury.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding tSAH in patients with mild and moderate injuries, there are conflicting results in the literature. Some studies found that a presence of tSAH on the first CT after trauma predicted a worse outcome (17)(18)(19). On the contrary, Demircivi et al (4) and Otsuka et al (20) reported that the presence of tSAH did not affect the outcome.…”
Section: European Head Injury Studies (Hit I and Ii) And The Americanmentioning
confidence: 87%
“…142 Higher doses in the range of 3-8 v,g" kg -l of fentanyl are even more effective.143-~4s The use of fentanyl for urgent intubations outside the operating room has also been shown to be free from adverse haemodynamic effects. 146 The duration of fentanyl analgesia is helpful as it continues to blunt sympathetic responses to the tracheal tube which persist after the completion of laryngoscopy, t47 Alfentanil in a dose as low as 10 Ixg" kg -) has been shown to have the efficacy ofa fentanyl dose of 2.5 Ixg' kg-l. 14s'149 Doses of alfentanil of 30 v.g" kg -~ blunt heart rate and blood pressure responses) s~ The pharmacokinetic profile of alfentanil may at times be helpful as it has a more rapid onset of action than fentanyl and a shorter half-life) s| Large doses of narcotics, while extremely effective, may cause chest wall rigidity which will be problematic if relaxants are not used) 41 Intravenous lidocaine has been used to blunt the haemodynamic response to intubation in the operating room and it may be considered for this purpose in the ICU. 152 Intravenous administration of lidocaine is clearly better than topical administration and, in fact, systemic absorption may be the responsible mechanism for the purported effects of topically applied lidocaine, ts3-156 Timing is important with an interval of three minutes reportedly being optimal between dosing and intubation.lS7 It should be noted, however, that this property of lidocaine has been questioned.tS~-~tl While the diminution of adverse haemodynamic effects by lidocaine is equivocal at best, there is no doubt that it will be helpful in decreasing the incidence of ventrieular extrasystoles associated with intubation.142'lss In the setting of cardiovascular disease, this anti-arrhythmic potential of lidocaine may be important.…”
Section: Coronary Artery Diseasementioning
confidence: 99%
“…In one series 3 % of such "stable" patients required emergency craniotomy. 41 PatientS with an intermediate range of function (GCS 7-11) will often require tracheal intubation. Indications for airway intervention include the need for therapeutic hyperventilation to prevent or treat intracranial hypertension, the delivery of adequate supplemental oxygen and protection of the airway from aspiration or obstruction.…”
Section: Head Injurymentioning
confidence: 99%